Can the same statistics module be used for service teaching by tailoring the support based on the student’s chosen qualification? - Calvert, Carol; Hilliam, Rachel; Steele, Emma (MSOR Connections, 2022)
At the Open University in the UK, students taking undergraduate degree qualifications in areas such as Data Science and Economics are now the largest cohort of students on a second-year undergraduate statistics module, originally written for specialist mathematics and statistics students. This paper outlines an ongoing project to identify how more targeted support could be provided to students who are studying non-mathematics and statistics qualifications. This has involved engaging all the tutors who provided support in the project to create a new way of adapting their teaching styles and tutorial content. By grouping students who had similar qualification goals together and linking these groups to individual tutors, the new way of working created an atmosphere where students feel able to share their own misunderstandings and see how statistics is useful within their chosen qualifications.